Determination of Orang Asli movement In Kampung Sungai Rual, Jeli, Kelantan - Hartini Husin (2013)
Orang asli are the indigenous minority peoples of peninsular Malaysia. Despite of proactive development initiated by the Malaysian Government in upgrading the quality of life of the orang asli communities since 1978, it is still difficult to develop an effective and suitable government's planning foundation and programmes for them because there are less information on their movements and daily routine activities. The absences of information on orang asli movements and behaviours have also delayed the development of effective land use strategies for orang asli development in Peninsular Malaysia. This study investigates the relationship of orang asli with their surrounding environment that influence their daily movement patterns. The orang asli Jahai is semi-nomadic. They did not moved out frequently from the settlement area. Majority of the orang asli Jahai in Kampung Sungai Rual are involved in oil palm and rubber plantation, and they are also involved in collecting forest product such as rattans and roots at the nearby forests. They are also sometimes attached to the agriculture activities inside the settlement. The orang asli Jahai in Kampung Sungai Rual involved in temporary occupation that depends on their environment. Currently, they are less mobile compared in the past Furthermore, the effects of development on the orang asli Jahai are determined. New development with more facilities is expanding in their own home range; their movement patterns are more circulated in this settlement only. The conclusion that can be made from the distribution map of orang asli movements is their movement patterns are more concentrated around the settlement only.